Poster Presentations 2017
DOI: 10.1136/annrheumdis-2017-eular.5460
|View full text |Cite
|
Sign up to set email alerts
|

THU0173 Long term safety and efficacy of filgotinib in a phase 2B open label extension study in patients with rheumatoid arthritis: results up to 144 weeks

Abstract: BackgroundFilgotinib (GLPG0634, GS-6034) is an oral JAK1 selective inhibitor with a favorable safety and efficacy profile in two 24-week Phase 2b studies as add-on to methotrexate (DARWIN 1) or as monotherapy (DARWIN 2) in patients with active rheumatoid arthritis (RA). Three daily doses were tested (50mg, 100mg or 200mg) in comparison to placebo.ObjectivesTo assess long term safety and efficacy of filgotinib 200mg daily in patients from the DARWIN 3 Phase 2 open-label extension study.MethodsPatients who compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Results of two other Phase IIa trials showed that filgotinib is generally well‐tolerated in RA subjects that had an insufficient response to MTX (Vanhoutte et al, 2017). This study was continued by two Phase IIb trials: randomized, dose‐finding study (DARWIN1; additive to MTX) and DARWIN2 (Single therapy; Alten et al, 2017). DARWIN 1 was designed on 594 RA subjects with a poor response to MTX (Westhovens, Alten, et al, 2016).…”
Section: Clinical Developmentsmentioning
confidence: 99%
“…Results of two other Phase IIa trials showed that filgotinib is generally well‐tolerated in RA subjects that had an insufficient response to MTX (Vanhoutte et al, 2017). This study was continued by two Phase IIb trials: randomized, dose‐finding study (DARWIN1; additive to MTX) and DARWIN2 (Single therapy; Alten et al, 2017). DARWIN 1 was designed on 594 RA subjects with a poor response to MTX (Westhovens, Alten, et al, 2016).…”
Section: Clinical Developmentsmentioning
confidence: 99%